2010
DOI: 10.1080/13504850802388993
|View full text |Cite
|
Sign up to set email alerts
|

Real exchange rates and bilateral trade dynamics of Turkey: panel cointegration approach

Abstract: The aim of this article is to analyse Turkey's bilateral trade dynamics with respect to a panel of seven countries. Employing several panel cointegration techniques, we show that the effect of a devaluation of Turkish currency on trade balance is country specific and there is no J-curve effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In the short run, the increase in the real exchange rate has no effect on the trade balance, while both domestic income and foreign income negatively affect the deterioration of the trade balance. The study of Celik and kaya (2010) aimed to analyze the dynamics of bilateral trade of Turkey with seven countries (France, Germany, Netherlands, Italy, Japan, United States, United Kingdom) using cross-sectional data during the period 1985 to 2006. The results showed that there is a long-run relationship between real exchange rates and real income with the trade balance, as the devaluation of the Turkish currency will improve the trade balance of Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the short run, the increase in the real exchange rate has no effect on the trade balance, while both domestic income and foreign income negatively affect the deterioration of the trade balance. The study of Celik and kaya (2010) aimed to analyze the dynamics of bilateral trade of Turkey with seven countries (France, Germany, Netherlands, Italy, Japan, United States, United Kingdom) using cross-sectional data during the period 1985 to 2006. The results showed that there is a long-run relationship between real exchange rates and real income with the trade balance, as the devaluation of the Turkish currency will improve the trade balance of Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies are criticized for suffering from aggregation bias in that they used trade flows between Turkey and rest of the world. To reduce the bias, Halicioglu (2007Halicioglu ( , 2008b and Celik and Kaya (2010) estimated bilateral trade balance models between Turkey and its trading partners and found mixed support for the J-curve effect. To reduce the aggregation bias further, Yazici and Klasra (2010) investigated response of two sectors of Turkish economy, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that holding green corporate bonds by the central bank may aid in managing the negative impact of climate change on financial stability.Second strand discusses the role of interest rates in climate change mitigation but through energy markets. Almahadin et al (2017),Benigno and Thoenissen (2008),Celik and Kaya (2010),Missio et al (2015),Sehrawat andGiri, (2017), andSokolov et al (2011) have shown that the impact of interest rates on economic performance is different amongst developing vs the developed world. Further, they have suggested that the stability of interest rates might yield a better performing economy.…”
mentioning
confidence: 99%